If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -6x + 5x = -6 Combine like terms: -6x + 5x = -1x 1 + -1x = -6 Solving 1 + -1x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = -6 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = -6 + -1 -1x = -6 + -1 Combine like terms: -6 + -1 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| -540+13.50=1500 | | 16=2(s-16)+8 | | 2-k=1 | | x(x-2)(x-6)=96 | | 15=3(d+1) | | 3n^2-2n+9=2 | | 4ab^2-3ab^2=1 | | 7n+3n-6n+2=18 | | (2)=(2)(b+(1)) | | (2x+24)+(4x-36)+6x=180 | | 13f=9 | | (2)=(2)(bt(1)) | | 2x+24+4x-36+6x=180 | | 15x-15=113+x | | p=4x+15 | | J-17=(3) | | 3x-10=62 | | 3x-12=15x+24 | | K+20=0 | | 2(g+7)=20 | | 34=0.4(p+22) | | 5n+12+3n=2n+30 | | 12/2=x/15 | | D-3=(2) | | r^3+3r=5 | | 3x-12=15x+8 | | 7x+1.5x=32560 | | 27(n-1)=3(6) | | 3r+13r=-16 | | (x-8)2+(y+2)2=49 | | 27n-1=18 | | 2m-3n=2 |